Influência da orientação corporal e do treino específico nos parâmetros espaço-temporais na emergência do alcance em lactentes - Cunha, Andréa Baraldi (2011)
Considering that changes in the organism s adaptability process occur in response to the convergent influence of intrinsic and extrinsic constraints, studies have shown that the body orientation and practice can positively influence the movements of the upper extremities in infants. Thus, this study has two objectives divided into two studies: (1) assess the influence of body orientation and (2) assess the specific training influence during reaching s emergence period. To meet the objectives proposed, the kinematic variables (spatio-temporal) were obtained through infants assessments at two positions: supine position and reclined at 45°, in a baby chair until 3 days after emergence of reaching. In Study 1, reaches were analyzed in these two positions. In Study 2, two assessments were performed: pre training and post training, i.e., before and immediately after training, respectively. To complete the training protocol, infants were divided into three groups: no training, supine training group and reclined training group. The results indicated that the different postures were not able to promote changes in reaching spatio-temporal parameters at the time this ability emerges. However, specific training was effective to promote faster reaches in infants in the reach s emergency phase, with recline training position being more appropriated than supine position. Moreover, the effects of training in specific positions were not transferable from one to another. Therefore, during the emergence period of reaching, infants have irregular trajectories and as this ability is fundamental for infants motor, social, perceptual and cognitive development, different positions and specific training can be used as intervention strategies to promote different sensory and motor experiences and thus provide different demands on the neuromotor system, promoting new movement strategies.